Occurrence of Albifimbria verrucaria in the Blood of a Female Child With Neuroblastoma - Masetti, Riccardo; Prodi, Antonio; Liberatore, Andrea; Carfagnini, Filomena; Cappelletti, Eleonora; Leardini, Davide; Pession, Andrea; De Carolis, Elena; Cricca, Monica (Frontiers in Medicine, 2020)
We report for the first time the occurrence of a filamentous fungus, Albifimbria verrucaria, in the blood of a pediatric neuroblastoma patient. The Albifimbria genus comprises common soil-inhabiting and saprophytic fungi and has been isolated as a plant pathogen in Northern and Southern Italy. As a human pathogen, A. verrucaria has been implicated in keratitis and can produce trichothecene toxins, which are weakly cytotoxic for mammalian cell lines. A. verrucaria was isolated from blood during the follow-up of a previous coagulase-negative Staphylococcus catheter-related infection. Lung nodules, compatible with fungal infection, had been observed on a CT scan 6 months earlier; they still persist. Possible routes of transmission were considered to be airborne, catheter related, or transfusion dependent, as the patient had undergone platelet and red blood cell transfusions during rescue chemotherapy. No filamentous fungi were isolated from sputum or CVCs. In conclusion, we describe an unprecedented fungemia caused by A. verrucaria and show how an unexpected pathogen may be acquired from the environment by patients at high risk due to immunosuppression. The route of transmission remains unknown.